A Temporalidade do Belo: Caminhos para uma filosofia da arte pós-idealista a partir de Gadamer - Santos, Cecília Mendonça de Souza Leão (2011)
The present paper consists in exploring the philosophical inquiries on aesthetic objects as developed by the german idealist tradition in order to evaluate how Hans-Georg Gadamer ´s take on the subject provides an overcoming of the said tradition. The role played by works of art in the history of philosophical thinking is accurately embodied by “Oldest Programme for a System of German Idealism”, which is profoundly connected to the constuction of modern subjectivity. Under the light of the desconstruction of the category of subject undertaken in the twentieth century, which took shape in the thought of Martin Heidegger, new parameters become necessary in order to properly understand the relationship of mankind with beings that exceed the concept of being “present-at-hand” (Vorhandenes) and manifest themselves as something radically different: the true works of art. Following that trail, we shall demonstrate how articulating a new conception of temporality, specific to the aesthetic being, allows philosophical hermeneutics to understand, by the standards of our own time, what sort of truth is disclosured in artworks. Through the proper regarding of the singularity of the temporal mode of being of artworks, which is given as simultaneity, we will show how works from the past become contemporary before our eyes. Recognizing the temporal mode of art´s existence opens a path for contemporary philosophy of art that by forgoing any normative criteria to define what is art, gains the ability to illuminate the phenomenon of transformation performed by such works in human existence – whether they may belong to the past or to our current time.